DAMPAK NEGATIF GAME ONLINE TERHADAP PRESTASI BELAJAR SISWA - Sinlae, Efriam; Dhiu, Margaretha (Penerbit Widina, Widina Media Utama, 2026)
This research aims to analyze the negative impacts of online games on student academic achievement. The phenomenon of online game addiction has become a serious problem in education that can disrupt concentration, study time, and student academic performance. The research method used is a literature study by analyzing various sources of scientific journals, books, and related research articles. The results show that online games have a significant negative impact on student learning achievement through several aspects: decreased effective study time, disruption of concentration and focus, changes in sleep patterns, decreased learning motivation, and physical and mental health disorders. Students who spend excessive time playing online games tend to experience declining academic grades, difficulty managing time, and lack of participation in learning activities. This research recommends the need for the role of parents, teachers, and counselors in providing guidance and supervision of online game use so that it does not interfere with student learning achievement.ABSTRAKPenelitian ini bertujuan untuk menganalisis dampak negatif game online terhadap prestasi belajar siswa. Fenomena kecanduan game online telah menjadi permasalahan serius dalam dunia pendidikan yang dapat mengganggu konsentrasi, waktu belajar, dan prestasi akademik siswa. Metode penelitian yang digunakan adalah studi literatur dengan menganalisis berbagai sumber jurnal ilmiah, buku, dan artikel penelitian terkait. Hasil penelitian menunjukkan bahwa game online memberikan dampak negatif signifikan terhadap prestasi belajar siswa melalui beberapa aspek, yaitu: penurunan waktu belajar efektif, gangguan konsentrasi dan fokus, perubahan pola tidur, penurunan motivasi belajar, dan gangguan kesehatan fisik serta mental. Siswa yang menghabiskan waktu berlebihan untuk bermain game online cenderung mengalami penurunan nilai akademik, kesulitan mengatur waktu, dan kurangnya partisipasi dalam kegiatan pembelajaran. Penelitian ini merekomendasikan perlunya peran orang tua, guru, dan konselor dalam memberikan bimbingan serta pengawasan terhadap penggunaan game online agar tidak mengganggu prestasi belajar siswa.